Digitalni begunci Transformacije migracijskih poti ali ko pametni telefon nadomesti kovček - Cukut Krilić, Sanja (ZRC SAZU, Založba ZRC, 2020)
The smartphone has become one of the main tenets of contemporary spatial as well as digital migration routes that are increasingly determined by technologies, platforms and networks. Such routes have become increasingly dangerous and uncertain, which testifies of structural criminalisation and control of people on the move, but also raises important questions about autonomy and agency of individuals as a response to restrictive migration and border policies. The monograph explores such transformations by focussing on the movement of refugees across the borders of nation-states through a rethinking of the notion of vulnerability (especially of women and children), the examination of perceptions of refugees and migrants by the public and a reflection of the notions of climate change and climate refugees that all challenge the main classificatory mechanisms constructing more or less "legitimate" groups of migrants. In this vein, the authors argue for more solidarity throughout the movement of individuals through the "gates" and "violent borders" of contemporary nation-states.